Species improvement and conservation of Aquilaria malaccensis Lam for yield management - Phukan Borpuzari, Papori; Debojit Saikia (Indian Journal of Agroforestry, 2023)
The present study was aimed for genetic improvement of Aquilaria malaccensis through selection from even aged 10-15 years individual infected trees on the basis of infection and vigour of infected individuals. A total number of 24 trees were selected from three different district of Assam and established seedling seed orchard at RFRI, Jorhat, Assam. The study also estimated the percentage of resinous lesions and numbers of insect injuries in the cut log before sending to the extraction industries. Average percentage of infected trees and infected area of a cut log is highest in Lalimsiga and lowest in Batipuria goan. Hence, the conservation of genetic diversity of the species has been worked out as a most useful sustainable management and efforts for log estimation study also has been made to develop a new part of research in natural infection study. As the infection occurs a very few selected trees hence, to develop and to focused on this study on different aspects of natural infection may be a very beneficial for this most economically important tree species.Key-words: Natural selection, seedling seed orchard, log estimation, conservation